(untitled) (Research, Society and Development, 2021)
This study aimed to understand and describe the challenges and benefits of the work carried out by an Association of Waste Pickers located in the southern region of Minas Gerais. For this, a basic qualitative study was carried out. The semi-structured interview was used as an instrument for data collection and for analysis, the coding technique. The President-Manager of the Association and an Associate were interviewed. Based on the results obtained, it was found that the biggest challenge for the Association is to ensure its subsistence, as it currently does not have significant support from the Public and Private Sectors and the little support it has is restricted to financial support. Due to the lack of knowledge and experience in management, waste pickers deal with poor management of their business. It was also found that the activity carried out by the Associations of Collectors contributes considerably to sustainability, whether in the economic sphere by enabling the reuse of many materials as raw material, in the environmental sphere by reducing the amount of waste deposited in nature and in the social sphere by providing a group that lives with economic inequality a way to guarantee their livelihood through their work.